Diagnóstico del mercado del arroz pilado en la zona comercial de la ciudad de Babahoyo - Avilés Lindao, Eduardo Dionicio (2019)
Rice cultivation has experienced tremendous growth due to the demand for its consumption, however the price divergence has affected so that the farmers do not obtain economic income according to their production costs. In our country, specifically the Province of Los Ríos, Babahoyo area, because it is located in the lower basin of the Guayas River and has a favorable temperature, water and climate, one of the main agricultural products produced is rice, generating income for the Farmers and sources of work for people who work in this important area. With the purpose of developing this document, surveys were carried out on ten people engaged in the purchase - sale of rice in the Babahoyo area. The surveys were made up of closed questions, which were tabulated and whose results were plotted in a pie chart. Subsequently, information was obtained from books, magazines, newspapers, scientific articles, web pages, papers that were submitted to the analysis and summary technique with topics related to the commercialization of the cultivation of rice. The conclusions determine that the majority of merchants in the Babahoyo area consider that the commercialization of rice is profitable; they sell the product at the reference price, they make it through credit to consumers or buyers, selling directors between 20 and 40 qq per month, according to the price and not the quality; Traders believe that there are problems in marketing the product, due to market competition and product quality and the commercialization of rice has undergone significant changes due to the weakening of several marketing practices and strengthening of mechanisms that have had an impact on prices and the marketing margins of this grass